The Uses of Artificial Intelligence in Psychological Counseling and Guidance: An Analytical Study - Almudhi, Hafsa Saleh; Albogami, Bara Mohammed; Alharbi, Nojod Melfi; Almuteri, Maryam Moteeb; Azab, Nouf Walid (Journal of Educational and Psychological Sciences, 2025)
This study discusses the contributions of artificial intelligence in the field of guidance and counseling, to determine the extent to which Arab studies utilize technological advancements to enhance counseling services, the study adopted the descriptive-analytical approach by analyzing Arab research that addressed the use of artificial intelligence in the field of psychological guidance and counseling, and the results of this study concluded that there is diversity in the uses of artificial intelligence in studies, including: (artificial intelligence systems and techniques for preparing guidance programs, artificial intelligence applications for mental health, standards for using artificial intelligence, automated education, artificial intelligence chat, and finally artificial intelligence panels), We confirm the existence of positive and effective results in the use of artificial intelligence in reducing symptoms of psychological anxiety and depression, and realizing self-awareness, psychological well-being, health level, and the effectiveness of the invitation effectiveness, but its effectiveness may lead to a negative impact, as the results see that future results of the use of artificial intelligence. technologies in the field of guidance and counseling are highlighted by artificial intelligence assistance in training briefs in the field of guidance and counseling, the number of uses of artificial intelligence technologies in guidance and counseling, which includes diverse participation on the hour, and assistance in psychological assessments. The study showed some advice, including: integrated artificial intelligence technologies to help provide specialized consultations, and support them around the clock, while ensuring their security.